O vestuário como cultura material : costurando a memória e a construção de si das mulheres em Maringá - Paraná - Franco, Rizia Ferrelli Loures Loyola (2014)
: The present ethnographic study consider women who are between 60 and 75 years, they live in Maringá-Paraná and they had anything to do with dressmaking. The aim is to investigate clothes they produced or got and was kept to reveal the social values. Thus, the dressing is analyzed as an element for its production through the bride dress, beauty pattern, shoes, socks, skirts and trousers that made the difference for these women in each phase and made them to belong to different social group. Besides, this is a female trace based on housewife, wife, mother and worker, showing modesty and care. Through this study, it was identified how the dressing builds the own identity and memory, mainly when family relationships are concerned. Knowing how to sew, a condition to get married, enriches the handmade work, t home, with love, while the ready consumed or the industrial machines utilization indicate technological advances. This way, the value f the new exists since the youth, but the access to novelties and to the variety was limited and used to contribute for social distinction among richer women.